2023
DOI: 10.3390/horticulturae9050547
|View full text |Cite
|
Sign up to set email alerts
|

The Dormancy Types and Germination Characteristics of the Seeds of Berberis koreana Palibin, an Endemic Species of Korea

Abstract: Berberis koreana Palibin is an endemic plant native to Korea. In this study, we aimed to study the seed germination of this species using a water imbibition experiment, gibberellic acid (GA3) treatment (0, 10, 100, or 1000 mg·L−1), cold stratification (0, 2, 4, 8, or 12 weeks at 4 °C), move-along experiment, and phenology studies. In the water imbibition experiment, the weight of the seeds increased by more than 120% in 24 h. An analysis of the internal and external morphological characteristics of the seed re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Seeds are typically dispersed during autumn and often overcome dormancy through the CS. Reports have indicated that seeds dispersed in autumn exhibit significant improvements in dormancy release following pretreatment with CS [ 20 , 24 , 44 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds are typically dispersed during autumn and often overcome dormancy through the CS. Reports have indicated that seeds dispersed in autumn exhibit significant improvements in dormancy release following pretreatment with CS [ 20 , 24 , 44 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the optimal conditions for seed propagation, the germination procedure for R. scandens seeds was conducted as follows: (1) a non-scarification treatment involving the endocarp, (2) an immersion in sulfuric acid (H 2 SO 4 , 96%) for varying durations (10,20,30,40,50, and 60 min) to assess its effect, (3) a mechanical scarification treatment without the total endocarp of seeds cut along the major axis using pruning shears, (4) an immersion in phytohormones (GA 3 1000 mg•L −1 , ≥90%, Sigma-Aldrich, St. Louis, MO, USA; and fluridone 30 µM, ≥90%, Sigma-Aldrich, St. Louis, MO, USA) for 24 h following ER, and (5) a CS (5 • C; RH of 70-90%; 4, 8, or 12 weeks) on a 1% agar medium following ER (Figure 5). After each CS, the seeds were germinated at an alternating temperature of 25/15 • C. For all seed germination experiments, the seeds were surface-sterilized by immersion in 2% NaClO for 5 min, followed by a thorough rinsing with distilled water.…”
Section: Seed Germination Following Scarification Phytohormone Treatm...mentioning
confidence: 99%
See 1 more Smart Citation